Special and differential treatment in GATT, the WTO and the FTAA - Ceara-Hatton, Miguel (2003)
Argues that Special and Differential Treatment (S&D) provisions have been undermined within the WTO and the FTAA reflecting changes in economic thought whereby development has been effectively excluded from the trade agenda.